Current management of diabetic retinopathy - Baumal, Caroline R.; Duker, Jay S. (St. Louis : Elsevier, 2018)
This book serves to discuss the risk factors and classification of diabetic retinopathy, followed by a chapter on each treatment modality. Clinicial cases are presented by the authors to demonstrate complicated diabetic reinopathy management issues -- From preface.
Epidemiology and natural history of diabetic retinopathy / Dante J. Pieramici, MD and Daniel Learned, MD -- Clinical diagnosis of diabetic retinopathy / Randee M. Watson, MD, Lindsay Machen, MD and Yannek I. Leiderman, MD, PHD -- Classification of diabetic retinopathy / Geraldine R. Slean, MS, MD and Rahul N. Khurana, MD -- Imaging in diabetic retinopathy / Caroline R. Baumal, MD -- Genetics of diabetic retinopathy / Karen Jeng-Miller, MD, MPH and Caroline R. Baumal, MD -- Effect of modifiable risk factors on the incidence and progression of diabetic retinopathy / Michael D. Tibbetts, MD -- Anti-vascular endothelial growth factor therapy for diabetic eye disease / Kendra Klein, MD and Michelle C. Liang, MD -- Corticosteroid therapy for diabetic retinopathy / Elad Moisseiev, MD and Anat Loewenstein, MD -- Laser treatment of diabetic retinopathy / Sean Platt, MD and Sophie Bakri, MD -- Surgical treatment of diabetic retinopathy / Mari? a H. Berrocal, MD and Alexandra Acaba? -- Treatment of diabetic retinopathy in pregnancy / Avni P. Finn, MD, MBA and Lejla Vajzovic, MD -- Novel treatments for diabetic retinopathy / David Eichenbaum, MD -- Clinical scenarios: introduction / cases from David Eichenbaum, MD, Darin R. Goldman, MD, Charles C. Wykoff, MD, Caroline R. Baumal, MD -- Summary of diabetic clinical research network (DRCR.net) protocols / Caroline R. Baumal, MD and Xuejing Chen, MD -- Diabetic terminology.
Includes bibliographical references and index.
Keywords: Diabetic Retinopathy